Memória de um trauma: melancolia e violência em Sinfonia em branco, de Adriana Lisboa - Parreira, Tálita Vicente (2022)
The present study aims to investigate how the representation of the traumatic memories of the protagonists Clarice and Maria Inês, in the novel Symphony in white (2013), by Adriana Lisboa, is configured as a process of melancholic construction, given the suffering that involves the memories of the characters, with bodies interdicted by the violence of an incestuous rape that guides the narrative construction of the work. The story of the two sisters dialogues with issues of urban reality, in the sense that the plot puts in debate situations that are constituted around violence and, in this way, is composed from the traumatic experience of Clarice's past. The narrative is constructed through temporal retreats and advances, with the presence of independent and interconnected memories. The rape committed by the sisters' father triggers a trauma in the characters that causes tensions in narrating the unspeakable, a result of the silence, the forbidden and the interdicts that drive the plot. Through the representation of these characters, it is possible to analyze the possibilities of reflection about the melancholic construction and traumatic transmission experienced by the protagonists, the affectionate relationships that reveal themselves frustrated between the characters, the loss of childhood, neglect, silence, as well as open wounds in memory, condition of women, their invisibility, oblivion and marginalization resulting from the tortuous consequences of lives interdicted by violence, but which in the end seek to overcome. In this context, in order to weave the process of memory construction imbricated with the concepts of violence, trauma and melancholy, it requires, from a bibliographic nature, the survey of theoretical-critical and literary texts concomitantly with readings and structuring of knowledge based on scholars such as Agamben (2002), Assmann (2011), Bordieu (2012), Beauvoir (1967), Dalcastagnè (2012), Favero; Rudge (2009), Ferenczi (1931/1933/1934), Figueiredo (2016), Freud (1996/1979/2014), Gagnebin (2009), Genette (s/d), Ginzburg (2012), Kristeva (1989), Ortalan (2016), Pellegrini (2008), Perrot (2003) Pinheiro; Quintella; Verztman (2010), Seligmann-Silva (2008/2002) among others.